Strategi Pengembangan Pariwisata Berbasis Ekonomi Kreatif dalam Peningkatan Perekonomian Masyarakat Kabupaten Toba Samosir - Hengki Mangiring Simarmata; Nora Januarti Panjaitan (Politeknik Bisnis Indonesia, 2019)
The purpose of this study was to formulate a strategy in the development of tourism based on creative economy in Ajibata Subdistrict, Toba Samosir Regency, especially in the two tourist villages of Parsaoran Sibisa Village and Sigapiton Village. This research will provide solutions and strategies to improve the economy of the local community, considering that Lake Toba is one of the strategic areas for national tourism. With the existence of the policy formulation, it is expected to be able to boost the income of the community around the middle to lower economic groups, bearing in mind the majority community as farmers and gardeners. The Research methods is descriptive using qualitative analysis. Data collection was carried out using interview techniques with the government of Toba Samosir Regency such as sub-district heads, village heads, tourism agencies, business operators, surrounding communities and tourist attractions. Data collection is also done by observation and documentation. Analysis techniques are performed using Interactive Analysis where the data collected is then reduced, presented data and draws conclusions. It is expected that with this research able to contribute and input in the development of creative economy-based tourism that is able to integrate the natural beauty, culture, culinary and local products in Toba Samosir Regency.